THE ANALYSIS OF ACER COMPUTER’S INTERNATIONALIZATION PROCESS FROM THE RESOURCE-BASED VIEW - HUANG, YING TZU (2009)
This paper focuses on the analysis of Acer Corporation’s internationalisation process from the Resource-Based view, RBV. Qualitative research method will be adopted in terms of the data collection throughout the entire research. It aims to examine the business strategies that Acer has adopted in terms of resources gathering and development. In addition, its internationalization pattern will also be compared and analyzed with the established theories such as the Uppsala Model, to see if it fits into any of those patterns. If not, the factors will be drilled and discussed based on the existing data regarding Acer’s development.